Unveiling Bullying in Education: A Sociological and Legal Inquiry - Manullang, Sardjana Orba (STAI Hubbulwathan Duri, 2024)
This research aims to enhance understanding of bullying in schools by applying a sociocultural theoretical framework. School bullying is a significant issue. The approach employed in this study involves doing a literature review by looking for relevant literature on the Scopus website. The retrieval procedure entails using specific keywords to search for articles on the Scopus website and subsequently analysing their relevance to the chosen keywords. The current literature review focuses on three primary themes: 1) The process of forming and understanding the concept of bullying; 2) The interpersonal aspect of bullying 3) Bullying as a component of an individual's life trajectory. The text discusses empirical findings for each topic to emphasise important issues, and presents arguments from relevant sociocultural theories to provide insight in each specific example. The findings demonstrate the potential for integrating diverse research on bullying and elucidating complicated phenomena. Considering sociocultural perspectives on bullying in schools has significant consequences for both study and practice. Bullying is influenced by the context in which it occurs, and it is important to consider the dynamics of relationships and the specific environments in which such behaviour takes place.